EP 40. Gynecomastia – A sign of a neuromuscular disease?. Issue 9 (September 2016) - Widmann, E.; Scheßl, J.; Schoser, B.
Abstract : Objective: The aim of a neurological examination is to narrow down by signs and symptoms which components of the neurological system are affected. In neuromuscular diseases non-neurological signs such as gynecomastia can be a valuable hint. Gynecomastia is defined as excess glandular growth of breast tissue in males, pathologically associated e.g. with testicular neoplasms or gonadal dysfunction [1, 2]. However there are also neuromuscular diseases such as spinal and bulbar muscular atrophy, myofibrillar myopathies and thyrotoxic hypokalemic periodic paralysispresenting with gynecomastia, we herby want to summarize. Methods: A systematic PubMed literature search was carried out by application of the search terms "spinal and bulbar muscular atrophy", "Kennedy's disease", "gynecomastia neuromuscular disease", "myopathy gynecomastia". Additionally, references in these articles were searched for further papers suitable to be included. Results: Spinal and bulbar muscular atrophy (Kennedy's disease, SBMA) is a slowly progressive adult onset neurodegenerative disorder, characterized by proximal muscle weakness and atrophy of the extremity and bulbar muscles, due to loss of lower motor neurons in the spinal cord and brainstem. It is caused by the expansion of a CAG repeat in the androgen receptor gene on the X Chromosome [3–6]. The length of the CAG expansion correlates inversely with age of disease onset and disease severity [7]. Up to 78% of patients present with gynecomastia due to partial androgen insensitivity [5, 8]. Desminopathies and Alpha-B crystallinopathies belong to the myofibrillar myopathies (MFM), a group of neuromuscular disorders, characterized by desmin-positive protein aggregations in muscle fibres and myofibrillar degeneration. They are caused by mutations in genes encoding for extramyofibrillar proteins (desmin (DES) and α B-crystallin (CRYAB)) [9, 10]. Desminopathies due to a variety of human desmin gene mutations on chromosome 2q35 cause different myopathy phenotypes, cardiac diseases and respiratory insufficiency [11, 12]. DES mutation (R350P) leads to a variability of clinical manifestation ranging from scapuloperoneal, limb girdle and distal phenotypes. Gynecomastia can be observed [13]. Alpha-B crystallinopathy due to mutations in the CRYAB gene presents with proximal and distal limb muscle weakness often associated with neck, trunk, and palatopharyngeal muscle involvement, cardiomyopathy and pulmonary insufficiency. Alpha-B Crystallin is a chaperone stabilizing desmin molecule by preventing its aggregation [14, 12]. Missense mutation p.Gly154Ser of CRYAB gene is associated with a late-onset distal vacuolar myopathy with protein aggregates. Mild gynecomastia can be present [15]. Thyrotoxic, hypokalemic periodic paralysis (THPP): Periodic paralysis associated with hyperthyroidism and hypokalemia is an uncommon disorder reported primarily in Asian males [1]. It is characterized by muscle paralysis and hypokalemia. Proximal muscles are more severely affected than distal muscles [17, 18] Uni- or bilateral gynecomastia can be a symptom even prior to the onset of paralysis [18, 19]. Conclusion: There is a limited range of neuromuscular disease associated with gynecomastia. Looking carefully at your patient whilst examination and noticing symptoms other than neurological symptoms can speed up to find the correct diagnosis, especially SBMA. Finally, most important, breast cancer has to be excluded, as there is an incidence of up to 2% in men.